The Impact of Divorce on Child Custody (Decision Study Number 150/Pdt.G/2021/PA.Btl) - Rahman, Abi Syauqi; Heriyani, Endang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Compilation of Islamic Law regulates the effects of divorce on children in Article 105 letter (a), which reads: "The maintenance of children who are not yet mumayyiz (under 12 years of age) is the right of the mother. The judge in the decision number 150/Pdt.G/2021/PA.Btl determines the custody of a child who has not yet matured in the hands of his father. This study aims to determine the consideration of the judge in determining the custody of a child who is not yet mumayyiz given to his father.This research is a normative legal research. The research data used are secondary data. Data collection techniques using secondary data are carried out through document studies. For data completeness, interviews with resource persons were also conducted. The primary and secondary data obtained were then analyzed descriptively and qualitatively.  The conclusion in this study is that the judge's consideration in decision number 150/Pdt.G/2021/PA.Btl, which gave custody of the first child aged 5 years to his father, because the mother was harsh with her first child and the child had lived with his biological father, so psychologically had more closeness to his father. Thus, the judge did not follow the provisions of Article 105 letter (a) of the Compilation of Islamic Law, which determines that the maintenance of children who are not yet mumayyiz or not yet 12 years old is the right of the mother.